Effect of lower urinary tract symptoms on the quality of life and sexual function of males in China, Taiwan, and South Korea: Subgroup analysis of a cross‐sectional, population‐based study. Issue 2 (11th March 2018) - Liao, Limin; Chuang, Yao‐Chi; Liu, Shih‐Ping; Lee, Kyu‐Sung; Yoo, Tag Keun; Chu, Romeo; Sumarsono, Budiwan; Wang, Jian‐Ye
Abstract : Objective: Lower urinary tract symptoms (LUTS) in males can reduce patients' quality of life (QoL) and affect sexual function and satisfaction. Although this has been documented in the US, Canada, Germany, Italy, UK, and Sweden, data are limited on the effects of LUTS on QoL and sexual function in Asian men. The present subgroup analysis of an Internet‐based survey correlated the incidence of male LUTS by severity and category with self‐assessed QoL and sexual function and satisfaction measures. Methods: Males aged ≥40 years were randomly selected from consumer survey panels in China, Taiwan, and South Korea. LUTS were defined using the International Continence Society (ICS) 2002 symptom definitions; symptom severity was assessed by the International Prostate Symptom Score (IPSS). The effect of LUTS on QoL was assessed using Patient Perception of Bladder Condition (PPBC) and IPSS QoL scores. Sexual function and satisfaction were assessed using the International Index of Erectile Function (IIEF). Results: Men with moderate‐to‐severe LUTS and overlap of voiding, storage, and post‐micturition symptom categories reported dissatisfaction with their QoL and sexual function. LUTS severity was negatively correlated with IIEF scores. Overlap of LUTS categories had a greater effect on QoL and sexual satisfaction than the incidence of just 1 LUTS. Conclusion: The findings of the present study suggest that LUTS is prevalent in >60% of Asian males aged ≥40 years and is associated with reduced QoL and sexual function, particularly in those with overlap of LUTS categories and greater symptom severity.